2021
DOI: 10.1007/s10554-021-02174-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute recoordination rather than functional hemodynamic improvement determines reverse remodelling by cardiac resynchronisation therapy

Abstract: Purpose: Cardiac resynchronisation therapy (CRT) improves left ventricular (LV) function acutely, with further improvements and reverse remodelling during chronic CRT. The current study investigated the relation between acute improvement of LV systolic function, acute mechanical recoordination, and long-term reverse remodelling after CRT. Methods: In 35 patients, LV speckle tracking longitudinal strain, LV volumes & ejection fraction (LVEF) were assessed by echocardiography before, acutely within three day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…The mechanical mechanisms associated with dysHF seem to be linked to left ventricular dyssynergistic contraction patterns resulting from dyssynchronous electrical activation leading to a shift in regional load during early myocardial contraction 33–35 . As demonstrated in figure , synergy seems to be a phenomenon linked to CRT that characterize patients responding to CRT.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanical mechanisms associated with dysHF seem to be linked to left ventricular dyssynergistic contraction patterns resulting from dyssynchronous electrical activation leading to a shift in regional load during early myocardial contraction 33–35 . As demonstrated in figure , synergy seems to be a phenomenon linked to CRT that characterize patients responding to CRT.…”
Section: Discussionmentioning
confidence: 98%
“…[ 33 ] These investigators also demonstrated that SRS was a more sensitive marker of the mechanical substrate for CRT response than the time interval between peak shortening in the various segments. [ 33 , 34 ] More recent studies corroborated these findings by showing that the sum of postero-lateral systolic pre-stretch and septal rebound stretch, called SSI, is strongly associated with clinical outcome after CRT. [ 35 , 36 ]…”
Section: Electro-mechanics During Biventricular Pacingmentioning
confidence: 91%
“…1.0 ± 2.0%) of SRSsept between different vendors was found by Van Everdingen et al, resulting in varying C-statistic values and different cut-off values [ 27 ]. Since a variability of up to 5% can be expected when measuring segmental strain [ 28 ], it is reasonable to suspect that, perhaps, similar amounts of variability were present in studies that investigated SRSsept (at rest) in a clinical setting [ 17 , 18 ]. Importantly, these studies have already proven the importance of SRSsept in the selection of patients with HF eligible for CRT, regardless of the underlying variability there.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic rebound stretch of the septum (SRSsept), and acute restoration thereof, has been demonstrated as a strong predictor of response to CRT before [ 3 , 17 , 18 ]. SRSsept is a promising deformation-based parameter because it reflects myocardial work inefficiency within the septum [ 19 ].…”
Section: Introductionmentioning
confidence: 99%